A revised nomenclature and classification for family-group taxa of parrots (Psittaciformes) - Joseph, Leo; Toon, Alicia; Schirtzinger, Erin E.; Wright, Timothy F.; Schodde, Richard (Zootaxa, 2012)
The last 20 years have seen a resurgence in systematic studies of parrots (Aves: Psittaciformes). Principally but not solelymolecular in nature, this body of work has addressed the circumscription of higher level groupings within the Psittaciformesand relationships among them. Stability has now emerged on many formerly contentious matters at these levels. Accordingly,we consider it appropriate to underpin further work on parrot biology with a freshly revised classification at the taxonomicranks spanned by family-group nomenclature, i.e., between superfamily and tribe. In light of the body of recent work, we advo-cate a framework of three superfamilies among parrots (Strigopoidea, Cacatuoidea and Psittacoidea) within which Linnaeantaxonomy can accommodate present phylogenetic understanding by employing groupings at the ranks of family, subfamily andtribe. Just as importantly, we have addressed numerous issues of nomenclature towards stabilising the family-group names ofparrots. We erect two new subfamily names, Coracopseinae Joseph, Toon, Schirtzinger, Wright & Schodde, subfam. nov. andPsittacellinae Joseph, Toon, Schirtzinger, Wright & Schodde, subfam. nov. We stress that rankings we have applied reflect thestate of understanding of parrot phylogeny and how it can be summarized in a Linnaean system; comparisons with rankings in other groups are likely not appropriate nor relevant.